Effectiveness of Media Video Technology Developments in The Community Towards IPS Learning Outcomes Student Motivation - Dian Nur Antika Eky Hastuti (Green Publisher Indonesia, 2021)
This research was conducted at SD Negeri 1 Candi, Mlarak District, Ponorogo Regency. The purpose of this research is to know 1) media which provide better learning outcomes IPS between the use of video and non-video media; 2) learning outcomes IPS is better between the have motivation to learn high, medium, and low ; 3) The learning outcomes better IPS between learning motivation high, medium, and low in each of the classes good use video and non-video media; 4) the results of social studies better between the use of video and non-video media in each state the motivation to learn. The design of this study using a quantitative approach with the quasi-experimental method with a factorial design. The results showed 1) media video provides better impact on learning outcomes IPS Elementary School fourth grade students 1 Candi; 2) learning outcomes IPS Elementary School fourth grade students 1 Candi who has a high motivation to learn is better than the one having the motivation to learn the medium, and; 3) In each class a good use of video and non-video media, learning outcomes IPS Elementary School fourth grade students 1 Candi who have high motivation to learn is better than the one having the motivation to learn the medium and low; and 4) In each of motivation to learn, the media video provides better impact on learning outcomes IPS Elementary School fourth grade students 1, Candi